Contrasting Effects of Geriatric Versus General Medical Multimorbidity on Quality of Ambulatory Care. Issue 9 (14th August 2014) - Min, Lillian; Kerr, Eve A.; Blaum, Caroline S.; Reuben, David; Cigolle, Christine; Wenger, Neil
<x xml:space="preserve">Abstract</x> Objectives To determine whether greater burden of geriatric conditions would have contrasting effects on quality of care (QOC) than nongeriatric, general medical conditions. Design Cross‐sectional observation over 1 year of ambulatory care. Setting The Assessing Care of Vulnerable Elders‐2 study. Participants Older adults prospectively screened for falls, incontinence, and dementia (N = 644). Measurements Participant‐level QOC in absolute percentage points calculated using 65 ambulatory care care‐process quality indicators (QIs) for 13 general medical and geriatric conditions (#QIs provided/#QIs eligible). Secondary outcomes were geriatric QOC (a subset of 38 geriatric care QIs) and medical QOC (the 27 remaining nongeriatric QIs). Exposure variables were number of six medical conditions (medical comorbidity) and six geriatric conditions (geriatric comorbidity), controlling for age, sex, number of primary care visits, and site. Results Medical and geriatric comorbidity were unrelated to each other (correlation coefficient = 0.04, P = .27) yet had opposite effects on QOC. Each additional medical condition was associated with a 3.2‐percentage point (95% confidence interval (CI) = 2.3–4.2 percentage point) increment in QOC, and each additional geriatric condition was associated with 4.9‐percentage point (95% CI = 3.5–6.5 percentage point) decrement in QOC. Participants with greater geriatric comorbidity received poorer medical and geriatric QOC. Conclusion Greater burden of geriatric conditions, or geriatric multimorbidity, is associated with poorer QOC. Geriatric multimorbidity should be targeted for better care using a comprehensive approach.